Sustainable Development Goals and livestock systems - Schneider, F.; Tarawali, Shirley A. (World Organisation for Animal Health, 2021)
Within the framework of the Sustainable Development Goals (SDGs) of the United Nations, particularly those that livestock impact most significantly (SDGs 1, 2, 3, 5, 8, 12, 13, 15 and 17), this paper provides an overview of the livestock sector’s impact on food system sustainability and opportunities for building solutions through sustainable livestock options that are supported by robust animal health services. The discourse is shaped by the experiences of the Global Agenda for Sustainable Livestock, a multi-stakeholder partnership which facilitates policy dialogue and action among diverse stakeholders to make livestock systems more sustainable. The Global Agenda for Sustainable Livestock adopted the aforementioned SDGs as the reference framework for its actions, which are organised under four domains (food and nutrition security, animal health and welfare, livelihoods and economic growth, and climate and natural resources). These domains are used to highlight the complexity and diversity of the livestock sector, its positive and negative relationships to development, the integral roles of animal health systems and the opportunities for livestock sector contributions towards a sustainable future.